Clinical outcome and hemodynamic behavior of the Labcor Dokimos Plus aortic valve. Issue 1 (December 2016) - Christ, Torsten; Zhigalov, Konstantin; Konertz, Wolfgang; Holinski, Sebastian
Abstract Background The Labcor Dokimos Plus (LDP) is a stented externally mounted pericardial aortic bioprosthesis, which was recently introduced in Europe. Aims of the study are evaluation of operative and postoperative results as well as hemodynamic performance. Methods One hundred consecutive patients with a mean age of 65.9 ± 10.7 years (range 35–87) and a mean EuroSCORE II of 3.1 ± 3.9 (range 0.67–24.5) underwent aortic valve replacement with the LDP. Mean valve-size was 25.2 ± 1.7 mm. Concomitant procedures were performed in 34% of the cases. Postoperative clinical data were analyzed and hemodynamic performance of the prostheses was evaluated by transthoracic echocardiography. Clinical follow-up was 100%, echocardiographic follow-up was 93% complete. Results Intraoperatively no peculiarities occurred. Mean cross clamp times for isolated and complex procedures were 74.5 ± 20.0 min and 103.7 ± 37.1 min, respectively. Patients were extubated after a mean of 9.4 ± 15.8 h. There were no perioperative strokes. Bleeding events occurred in 4 patients. 30-day-mortality was 2%. One case of early endocarditis occurred. Echocardiography showed maximum and mean pressure gradients of 18.1 ± 6.4 and 9.6 ± 3.7 mmHg, respectively. Correspondingly to valve sizes 21, 23, 25 and 27 mm, mean pressure gradients were 17.3, 9.5, 8.5 and 10.2 mmHg, effective orifice areas were 1.92, 1.79, 2.0, 2.16 cm2 and indexed effective orifice areas were 1.08, 0.95, 0.99 and 1.01 cm2 /m2, respectively. No relevant regurgitations occurred. Conclusions The LDP showed operatively no peculiarities and a satisfactory clinical outcome with low perioperative morbidity and mortality. The hemodynamic performance of the implanted valve sizes was satisfactory.